Whom Should a Christian Vote? Facing Identity Politics from Biblical Perspective on Presidential Election - Sabdono, Erastus; Hedianto, Lonato; Novalina, Martina; Andri, Andri; Sunardi, Philipus (Millah: Journal of Religious Studies, 2024)
Indonesia stands firm in its democratic values and respects its presidential election in 2024. However, the scent of the history of identity politics still lingers and threatens the harmony of voting. Even though identity politics seem to be a common and acceptable method, it bears danger, especially to Christians as a minority. This can happen through the burdens and biases of Christians to vote. Through descriptive literature methods of biblical perspective with contextual interpretation alongside political reviews and literature, this paper tries to answer the question of how a Christian should vote for their future leader amidst the pressure of identity politics. The Bible can be a clear guideline to show that such political events and methods had already occurred in the Old Testament and New Testament eras. The wisdom contained in the Proverbs that was intended for future young leaders, as well as the wisdom of Jesus Christ, can help shape the answer on how a Christian should vote for their future leaders. This paper finds that Christians as minorities should try to be objective following biblical standards and the quality of a leader, such as righteousness, multiple councils, servanthood, and accountability, rather than drowning in misconceptions of defensive and subjective votes based on religion-ethnicity sameness or popular opinion.